NORM inventory forecast for Australian offshore oil and gas decommissioned assets and radioactive waste disposal pathways - McKay, Scott; Higgins, Stuart; Baker, Peter (Australian Petroleum Production and Exploration Association, 2020)
This research establishes a decommissioning timeline for the existing oil and gas facilities across all of the Australian offshore oil and gas production basins. Minimal data exist in the public domain to estimate these decommissioning timelines and, more importantly, the significant waste volumes generated; including potentially hazardous wastes such as naturally occurring radioactive material (NORM). At this time there is no approved onshore radioactive waste disposal pathway in Australia to accommodate this material. Applying an estimation methodology, based on Norwegian decommissioning data with regional activity factors, allows a NORM waste forecast to be established for the decommissioning of Australian oil and gas offshore infrastructure. The total NORM disposal burden is estimated to be in the range of 223–1674 tonnes for decommissioning activity to 2060, with over 68% of this material generated between 2018 and 2025. Due to the sparsity of public domain data this forecast is deemed to be uncertain and excludes the NORM contamination anticipated to be present in subsea export pipelines, trunklines and well production tubing. Current regulations governing the categorisation and disposal of radioactive wastes across Australia are complex and regionally dependent. This regional variation makes the implementation of a national radioactive waste disposal facility more difficult, and encourages the export of radioactive wastes overseas for final disposal. Exporting of radioactive wastes potentially presents a higher risk compared with in-country disposal and is likely not an effective long-term proposition. A comprehensive NORM data collection and quantification assessment programme, spanning all onshore and offshore oil and gas infrastructure, needs to implemented to drive and verify a NORM waste management strategy for the wave of facility decommissioning projects that are fast approaching.